التفويض التشريعي - د.سيفان باكراد ميسروب (PROSPECTIVE RESEARCHES, 2023)
The constitution grants every authority a certain function which is independent from the other authority. So, no authority should authorize its specialities any other one. But, the breadth and branching of the state functions in the current time and the need to deal with the economic, social and political crises that overwhelmed several states has made a pressing need for authorizing the executive authority to practice legislative tasks by an empowerment from the constitutional legislator in order to put an end to those crises on condition that this empowerment shouldn’t be a justification for the executive authority to transgress the functions of other authorities in the state, because the legislative authorization is considered an exception that cannot be expanded or granted unless there are unusual circumstances and within limited terms that have been stipulated in the constitution. In fact, the legislative authorization is regarded as a serious weapon in the hand of the legislative authority that is granted to the executive authority in accordance with constitution rules, because those legislations are characterized by the power of law if they are ratified by the parliament and that can expose the basic rights and freedoms to a great danger, and that necessitates the availability of sufficient guarantees when resorting to authorization. The judicial control is considered the most effective guarantee.